Islam dan Sejarah Sosial Modern: Siasat Usaha Pedagang Kaki Lima (PKL) dengan Pemanfaatan Hubungan Komunitas PKL Muslim Pasar Suak Bato 26 Ilir di Palembang - Mohammad Syawaludin Ibrahim (Fakultas Adab dan Humaniora UIN Raden Fatah, 2018)
The main subject of this research that is; Streer traders form a community and use it as a business tactics that make an important contribution to the value of their welfare. Including this section of research is to explain in depth the pattern of Muslim street traders community relationships and forms of community use as a business tactic. With the theory of parson structural functionalism in assisting with the social network theory of Luhkmanns and the value exchange theory of Homas, the framing of the relationship between the Muslim street traders community relationship with the value of benefit and welfare value is used to explain the activities of the social system and the daily activities of the street vendors. The phenomenology of this research explores in depth the process, meaning, and understanding of experience and appreciation that occurs in social relationships in the relationship of Muslim street vendors. Keywords: Street Traders, Community, Business Strategy, Value of material welfare And In materials, Cybernetics.